2014
DOI: 10.1016/j.stemcr.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Induction Promotes Corneal Epithelial Cell Differentiation from Human Induced Pluripotent Stem Cells

Abstract: SummaryHuman induced pluripotent stem cells (hiPSCs) offer unique opportunities for developing novel cell-based therapies and disease modeling. In this study, we developed a directed differentiation method for hiPSCs toward corneal epithelial progenitor cells capable of terminal differentiation toward mature corneal epithelial-like cells. In order to improve the efficiency and reproducibility of our method, we replicated signaling cues active during ocular surface ectoderm development with the help of two smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 66 publications
2
87
0
1
Order By: Relevance
“…Cell replacement therapy using autologous or allogeneic adult limbal grafts has been the standard treatment for patients with severe limbal stem cell deficiency (LSCD) (Rama et al, 2010;Sangwan et al, 2011;Basu et al, 2016). However, in the case of bilateral epithelial defects and for the treatment of conditions affecting the stromal and endothelial cell layers, alternative stem cell sources such as embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) have been explored with a view to generating the various corneal cell types (Ahmad et al, 2007;Shalom-Feuerstein et al, 2012;Hayashi et al, 2012;Sareen et al, 2014;Mikhailova et al, 2014;Chan et al, 2013;Zhang et al, 2014;Chen et al, 2015;McCabe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cell replacement therapy using autologous or allogeneic adult limbal grafts has been the standard treatment for patients with severe limbal stem cell deficiency (LSCD) (Rama et al, 2010;Sangwan et al, 2011;Basu et al, 2016). However, in the case of bilateral epithelial defects and for the treatment of conditions affecting the stromal and endothelial cell layers, alternative stem cell sources such as embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) have been explored with a view to generating the various corneal cell types (Ahmad et al, 2007;Shalom-Feuerstein et al, 2012;Hayashi et al, 2012;Sareen et al, 2014;Mikhailova et al, 2014;Chan et al, 2013;Zhang et al, 2014;Chen et al, 2015;McCabe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some significant efforts have already been made in these areas [2, 11]. Moreover, studies utilizing directed differentiation from iPS or ES cells to drive primitive cells to a lacrimal fate may require an understanding of the expression of genes in adult tissue [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Directed differentiation experiments [20,30], in which immature stem cells are differentiated into mature cell types using changes in gene expression depend on a detailed understanding of critical developmental factors. Several studies have demonstrated the ability of stem cells to be differentiated into ectodermal cell types, but none have been reported on directing differentiation into lacrimal epithelial cells [20]. We believe a strong understanding of the differential gene expression and signaling pathway differences between lacrimal gland and other ectodermal tissue types will be critical in the advancement of stem cell methodologies to create lacrimal epithelium in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…This method utilizes a feeder layer and a differentiation medium [30]. Consequently, several groups followed similar protocols, most of them used Collagen type IV as coating material as this is the most abundant basement membrane component of the cornea [3133]. Collagen type IV promotes the proliferation of p63-positive cells, a marker for corneal epithelial cells [34], though it is quite expensive.…”
Section: Discussionmentioning
confidence: 99%